KINETIC MECHANISM OF OXYGEN ISOTOPE DISEQUILIBRIUM IN PRECIPITATED WITHERITE AND ARAGONITE AT LOW TEMPERATURES: AN EXPERIMENTAL STUDY - Zhou G.T.; Zheng Y.F. (My University, 2002)
To study what dictates oxygen isotope equilibrium fractionation between inorganic carbonate and water during carbonate precipitation from aqueous solutions, a direct precipitation approach was used to synthesize witherite, and an overgrowth technique was used to synthesize aragonite. The experiments were conducted at 50 and 70°C by one- and two-step approaches, respectively, with a difference in the time of oxygen isotope exchange between dissolved carbonate and water before carbonate precipitation. The two-step approach involved sufficient time to achieve oxygen isotope equilibrium between dissolved carbonate and water, whereas the one-step approach did not. The measured witherite-water fractionations are systematically lower than the aragonite-water fractionations regardless of exchange time between dissolved carbonate and water, pointing to cation effect on oxygen isotope partitioning between the barium and calcium carbonates when precipitating them from the solutions. The two-step approach experiments provide the equilibrium fractionations between the precipitated carbonates and water, whereas the one-step experiments do not. The present experiments show that approaching equilibrium oxygen isotope fractionation between precipitated carbonate and water proceeds via the following two processes: Oxygen isotope exchange between [CO3]2- and H2O: (1)[C16O3]2-+2H218O=[C18O216O]2-+2H216OA combination of divalent metal cation M2+ with the [CO3]2- to form carbonate: (2)M2++[C18O216O]2-+H218O=MC18O3+H216O Reaction 1 is the rate-limiting step for equilibrium oxygen isotope fractionation between carbonate and water, and reaction 2 bears the structural effect of carbonate crystallization on oxygen isotope fractionation during carbonate precipitation. The present results show that the time of [CO3]2--H2O isotope exchange in the precipitation experiments is of critical importance in dictating the extent of isotopic equilibration between precipitated carbonate and water. If the time of oxygen isotope exchange between [CO3]2- and H2O is long enough to attain equilibrium before carbonate precipitation, the precipitated carbonate is able to achieve isotopic equilibration with water.